THE RELATIONSHIP BETWEEN MOTHER'S BEHAVIOR IN SEEKING TREATMENT WITH THE RECURRENCE RATE OF PNEUMONIA AMONG CHILDREN UNDER FIVE - Supiani Supiani; Mufdlilah Mufdlilah; Djauhar Ismail (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Introduction: Pneumonia is a global problem with a significant cause of death for more than 2 million children under five every year. Mothers’ behavior in seeking treatment is one of the main factors of delay in getting proper treatment by increasing the risk of recurrence pneumonia among children under five. This study aimed to investigate the relationship between the mother's behavior in seeking treatment with the recurrence rate of pneumonia among children under five. Method: This research method was an observational analytic study with the cross-sectional approach. The number of samples in this study was 47 mothers with toddlers pneumonia. The sampling technique was using purposive sampling and data analysis used Chi-square and multiple logistic regression. Result: The study found, there was a relationship between the mothers’ behavior in seeking treatment with the recurrence rate of pneumonia among children under five (PR = 12,000; CI95%=2,275-63,285; p = 0.003). One of confounding variables namely the cost of treatment had relationship with the recurrence rate of pneumonia. Whereas the variables of mother's knowledge, access to services, and distance of residence are not related to the recurrence rate of pneumonia in infants. The results of multiple logistic regression analysis found that mothers’ behavior in seeking of the treatment, treatment cost, and distance of residence affect 51.2% of the recurrence rate of pneumonia among children under five in Yogyakarta. Conclusion: The mothers’ behavior in seeking treatment, the cost of treatment, and distance of residence affect the recurrence rate of pneumonia among children under five.